The Antimicrobe of Kaempferia galanga L. Rhizome against Microsporum canis and Staphylococcus epidermidis – In-vitro Study - Kiki Nurtjahtja (International Journal of Ecophysiology, 2022)
This study aims to determine the ability of ethanolic extract of Kaempferia galanga L. rhizome in inhibiting the growth of Microsporum canis and Staphylococcus epidermidis. Rhizome concentrations used were 40, 50, 60, and 70%. Each treatment was replicate 4 times. Results showed that extract of K. galanga rhizome up to 70% have not significantly differences against M. canis and S. epidermidis. Rhizome extract of 70% inhibit the growth of M. canis with the highest inhibition 5.88 mm (in compared to ketoconazole 10.35 mm). Whereas the extract of 70% inhibit S. epidermidis with the highest inhibition 3.16 mm (in compared to chloramphenicol 25.49 mm).